Imaging Shear Strength Along Subduction Faults. Issue 22 (18th November 2017) - Bletery, Quentin; Thomas, Amanda M.; Rempel, Alan W.; Hardebeck, Jeanne L.
Abstract: Subduction faults accumulate stress during long periods of time and release this stress suddenly, during earthquakes, when it reaches a threshold. This threshold, the shear strength, controls the occurrence and magnitude of earthquakes. We consider a 3‐D model to derive an analytical expression for how the shear strength depends on the fault geometry, the convergence obliquity, frictional properties, and the stress field orientation. We then use estimates of these different parameters in Japan to infer the distribution of shear strength along a subduction fault. We show that the 2011 M w 9.0 Tohoku earthquake ruptured a fault portion characterized by unusually small variations in static shear strength. This observation is consistent with the hypothesis that large earthquakes preferentially rupture regions with relatively homogeneous shear strength. With increasing constraints on the different parameters at play, our approach could, in the future, help identify favorable locations for large earthquakes. Plain Language Summary: Subduction faults accumulate stress during hundreds of years until this stress reaches a threshold. When this threshold is reached, an earthquake occurs. We derive an expression of the rupture threshold depending on different physical parameters, which vary along subduction faults. We then use estimates of the spacial variations of these different parameters in Japan to infer the distribution of the rupture threshold along the Japanese subduction faults. Our results suggest that very large earthquakes, such as the 2011 M w 9.0 Tohoku earthquake, occur on fault portions of particularly homogeneous rupture thresholds. Our interpretation is that the rupture threshold is more likely to be reached simultaneously on broad fault portions if it does not vary much from one point of the fault to another. Imaging spatial variations of the rupture threshold along large faults may then reveal the location of possible future large earthquakes. Key Points: We relate earthquake rupture threshold to physical parameters We estimate the variation of the rupture threshold along an actual subduction fault We relate estimates of rupture threshold variations to earthquake magnitude